A Review on the Use of Moxifloxacin in Multidrug Resistant Tuberculosis - D, Praveen; Vivean S, Priya Rajam; Priya J, Shanmuga (Genes Review, 2015)
The first line anti-tuberculosis drugs have shown an increasing prevalence of resistance. The higher incidence of TB has led to stronger requirements of other therapies apart from the World Health Organisation recommended Directly Observed Therapy in Short course (DOTS). New drugs highly effective against Mycobacterium tuberculosis (MTB) could enhance the treatment of cases with resistance to first line drugs (isoniazid and rifampicin) and may curtail the extent of present regular regimes. Fluoroquinolones are reasonably effective against Mycobacterium tuberculosis (MTB). They have been used as alternative for some present first-line drugs such as Isoniazid, and have been efficient even in Multi Drug Resistant Tuberculosis. These efforts must be further enhanced to ensure ultimate success in discovering, developing, and delivering drastically improved therapies for tuberculosis patients.